Becoming a school consultant : lessons learned - Rosenfield, Sylvia A. (New York : Routledge, 2012)
Most consultation courses in school psychology focus heavily on theoretical models of consultation and associated intervention procedures. Little time is devoted to developing communication and process skills. Yet these process skills are key to properly identifying student problems and selecting appropriate interventions. Without skillfully conducted consultations, implementation and evaluation of an intervention can be minimal. This book is designed to help students develop the process skills needed to become effective school consultants in consultee-centered consultation, with special emphasis on the instructional consultation model. The authors address specific skills and issues faced by novice consultants and documents how they worked through particular issues that are likely to occur in school consultation practice"
Includes bibliographical references and index.
Keywords: Educational consultants; EDUCATION / General